2023
DOI: 10.3892/ol.2023.13774
|View full text |Cite
|
Sign up to set email alerts
|

Impact of two‑field or three‑field lymphadenectomy on overall survival in middle and lower thoracic esophageal squamous cell carcinoma: A single‑center retrospective analysis

Abstract: Squamous cell carcinoma is the main subtype of esophageal cancer in East Asia. The effect of the number of lymph nodes (LNs) removed to treat middle and lower thoracic esophageal squamous cell carcinoma (ESCC) in China remains controversial. Therefore, the present study aimed to investigate the impact of the number of LNs removed during lymphadenectomy on the survival of patients with middle and lower thoracic ESCC. Data were obtained from the Sichuan Cancer Hospital and Institute Esophageal Cancer Case Manage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…Tachimori et al . proposed that the zones of LN metastasis and tumor locations had different efficacy indexes (EI) in their outcomes; this was further verified in the Chinese data 19 , 23 , 24 . Their study has revealed that the 5-year OS rate for patients with LNM in the supraclavicular region was 27.7–60.7%.…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“…Tachimori et al . proposed that the zones of LN metastasis and tumor locations had different efficacy indexes (EI) in their outcomes; this was further verified in the Chinese data 19 , 23 , 24 . Their study has revealed that the 5-year OS rate for patients with LNM in the supraclavicular region was 27.7–60.7%.…”
Section: Discussionmentioning
confidence: 73%
“…Lymph node metastasis (LNM) is a critical factor in determining the prognosis of individuals with thoracic ESCC, reflecting the degree of disease spread and the potential for systemic dissemination 16 18 . Lymphadenectomy is crucial in the surgical procedure of esophagectomy 19 . In 1990, Isono et al .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… 24 However, the extent of lymphadenectomy in esophagectomy still is a topic of continued discussion. 18 – 20 , 25 , 26 Considering the pattern of metastasis in ESCC, LN stations have certain clinical value and are gaining increased importance. 8 , 27…”
Section: Discussionmentioning
confidence: 99%
“… 6 , 7 , 9 , 16 Lymph node (LN) metastasis (LNM) poses a significant challenge to the curative effect of the standard treatment options. 17 20 …”
mentioning
confidence: 99%